If x satisfy the equation 4 x − 4 x − 1 = 2 4 , find the value of ( 2 x ) x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I will help you to modify your solution by using the L A T E X codes
4 x − 4 x − 1 = 2 4
⇒ ( 2 x ) 2 − 4 x / 4 = 2 4
⇒ ( 2 x ) 2 − ( 2 x ) 2 / 4 = 2 4
Let 2 x = a then a 2 − a 2 / 4 = 2 4
3 a 2 / 4 = 2 4
3 a 2 = 9 6
= a 2 = 3 2
But a = 2 x then 2 x 2 = 3 2 = 2 2 x = 2 5 then = 2 x = 5 = x = 5 / 2
And value of = 2 x x = ( 2 × 5 / 2 ) 5 / 2 = 5 5 / 2 this is equal to 2 5 5 ?
This is based on your solution by using your natural solution.
Log in to reply
that is better and good solution...+1
Thank you cedie camomot
Log in to reply
Your welcome ⌣ ¨ practice L A T e X soon
Brilliant..!! the answer is now much More attractive and easy to understand.+1
good solution but use latex to be more clear...+1
Thanks for sharing your approach. (+1) You can insert a line break by leaving three spaces at the end of the line. I have edited your solution accordingly.
Nice sol. Did it the same way..!
Great solution , same way, +1 :)
4 x − 4 x − 1 = 2 4 4 x − 4 4 x = 2 4 4 x ( 1 − 4 1 ) = 2 4 4 x ( 4 3 ) = 2 4 4 x = 2 4 × 3 4 4 x = 3 2 2 2 x = 2 5 2 x = 5 x = 2 5 ( 2 x ) x = ( 2 × 2 5 ) 2 5 = 5 2 + 2 1 = 5 2 × 5 2 1 = 2 5 5
love this answer, it shows it so clearly
2 2 x − 2 2 x − 2 = 2 3 × 3
2 3 2 2 x − 2 2 x − 2 = 3
2 2 x ( 8 1 − 3 2 1 ) = 3
2 2 x = 3 2
x = 2 5
∴ ( 2 x ) x = ( 2 × 2 5 ) 2 5 = 2 5 5
in step 2:how did 2 2 x − 2 become 2 2 x − 5 ?
Log in to reply
It was typo...thanks!!
Log in to reply
it is was a pleasure to help you as you had a different answer.
Maybe a faster solution here: 4 x − 4 x − 1 = 2 8
⇒ 3 ∗ 4 x − 1 = 3 ∗ 8
⇒ 2 2 ∗ ( x − 1 ) = 2 3
⇒ 2 x − 2 = 3
⇒ x = 5 / 2
⇒ ( 2 x ) x = 5 5 / 2 = 2 5 ∗ 5
Your solution is a mess.
The original equation is 4 x − 4 x − 1 = 2 4
And how did you get 3 × 4 x − 1 = 3 × 8 ?
Log in to reply
I agree with you.that was a wrong solution from damien G
He means 24 = 3 x 8 and 4 x − 4 x − 1 = ( 4 − 1 ) ( 4 x − 1 ) = 3 ∗ ( 4 x − 1 )
Log in to reply
Ah, I see. Now I understand
now i understood what he meant to say.
4
x
−
4
x
−
1
=
4
x
×
4
−
1
=
(
4
x
)
(
1
−
4
1
)
=(
4
x
)
(
4
3
)
=
3
×
(
4
x
−
1
)
now i understood what he meant to say.
4
x
−
4
x
−
1
=
4
x
×
4
−
1
=
(
4
x
)
(
1
−
4
1
)
=(
4
x
)
(
4
3
)
=
3
×
4
x
−
1
Take out 4 x − 1 common and cancel 3 from both sides to get x=2.5 and then put in the required answer
good observation
Log in to reply
Why not +1
Log in to reply
ok,I have given!!!
=4^x(1-.25)=4^2.5>>>>>>> x=2.5 >>>>
can you be clear in writing your solution by using latex.
Problem Loading...
Note Loading...
Set Loading...
4^x - 4^(x-1) = 24
=(2^x)^2 - 4^x/4 = 24
=(2^x)^2 - (2^x)^2/4 =24
Let 2^x=a then
=a^2 - a^2/4 =24
=3a^2/4 =24
=3a^2 = 96
=a^2 = 32
But a=2^x then
=(2^x)^2 = 32
=2^2x = 2^5 then
=2x = 5
=x= 5/2
And value of
=(2x)^x
=(2×5/2)^5/2
=5^(5/2) this is equal to 25×sqrt(5)